2009
DOI: 10.2174/1874325000903010022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Incisional Continuous Regional Block on Early and Late Postoperative Conditions in Tibial Osteotomy and Total Knee Arthroplasty

Abstract: Background:Postoperative regional anesthesia hastens recovery and reduces the length of hospital stay of orthopedic surgical patients. This study was designed to assess the impact of pre-incisional continuous femoral block on postoperative conditions (POC) of tibial osteotomy and total knee arthroplasty patients.Methods:After insertion of a femoral catheter under peripheral nerve stimulation control, 111 patients scheduled for total knee arthroplasty or tibial osteotomy were randomized to receive either pre-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Various studies have found pain reduction and opioid-sparing benefits of RA in total knee arthroplasty using adductor canal or femoral nerve blockade. 24 In patients undergoing tibial osteotomy, Motamed et al 25 found preoperative continuous femoral nerve blockade decreased length of stay and duration of rescue morphine requirements. While the same blocks may be used for tibial plateau fractures, factors such as acuity of pain, soft tissue injury, and inflammation may lead to a greatly different experience of pain in the trauma patient, limiting the generalizability of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found pain reduction and opioid-sparing benefits of RA in total knee arthroplasty using adductor canal or femoral nerve blockade. 24 In patients undergoing tibial osteotomy, Motamed et al 25 found preoperative continuous femoral nerve blockade decreased length of stay and duration of rescue morphine requirements. While the same blocks may be used for tibial plateau fractures, factors such as acuity of pain, soft tissue injury, and inflammation may lead to a greatly different experience of pain in the trauma patient, limiting the generalizability of these studies.…”
Section: Discussionmentioning
confidence: 99%